Peran Bimbingan dan Konseling Islam dalam Meningkatkan Kedisiplinan Siswa Kelas VIII MTS Negeri 1 Wonosobo - Rizki Nurfaizi; Sri Haryanto (Moral : Jurnal kajian Pendidikan Islam, 2024)
Student discipline refers to the attitude of obedience shown by students in a school towards the applicable rules, norms, and regulations. This level of discipline can be measured through students' obedience in following the rules related to study hours and their obedience in participating in other school activities. Each student has a different level of error, which is caused by the characteristics of each individual. Therefore, the role of guidance and counseling teachers is very important in improving student discipline in the school environment. In this study, the author asks the question: How does Islamic guidance and counseling contribute to improving student discipline at MTs Negeri 1 Wonosobo? The purpose of this study is to understand the role of Islamic guidance and counseling in improving student discipline at the institution. The author uses a qualitative field research approach, with primary data sources consisting of guidance and counseling teachers and students. Data collection was carried out through interview, observation, and documentation methods.The results of the study indicate that Islamic guidance and counseling plays an important role in improving student discipline at MTs Negeri 1 Wonosobo by helping students solve problems, providing advice and reprimands to those who are less disciplined, providing direction so that students can make the right decisions, and providing advice and reprimands. In addition, efforts made by guidance and counseling teachers to prevent indiscipline include through group guidance, individual guidance, and involving parents.